2023
DOI: 10.1177/03000605231218619
|View full text |Cite
|
Sign up to set email alerts
|

Oral mucosal diseases and psychosocial factors: progress in related neurobiological mechanisms

Huirong Zhou,
Xiaoping Lin

Abstract: The aetiology of oral mucosal diseases, such as recurrent aphthous ulcer (RAU), oral lichen planus (OLP) and burning mouth syndrome (BMS), involves many factors, and it remains difficult for clinicians to effectively relieve disease symptoms and formulate coping strategies. With the rapid development of psychology, the role of mental and psychological factors in RAU, OLP and BMS has gradually attracted researchers attention, but the specific mechanism has not been completely determined. This narrative review d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 44 publications
1
1
0
Order By: Relevance
“…The results of our study revealed significantly escalated levels of depression, anxiety, and stress in the patients with RAS as opposed to those without the condition. These results were consistent with the findings of other studies [7,14], where elevated levels of depression, anxiety, and stress were observed in participants with a history of RAS. According to Gallo et al, psychological stress may serve as a trigger or moderating element in RAS-afflicted patients [15].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results of our study revealed significantly escalated levels of depression, anxiety, and stress in the patients with RAS as opposed to those without the condition. These results were consistent with the findings of other studies [7,14], where elevated levels of depression, anxiety, and stress were observed in participants with a history of RAS. According to Gallo et al, psychological stress may serve as a trigger or moderating element in RAS-afflicted patients [15].…”
Section: Discussionsupporting
confidence: 93%
“…Ziaudeen et al found that psychological stress in RAS patients disturbed the oxidant-antioxidant balance, leading to oxidative stress and the onset and persistence of aphthous ulcers [17]. Psychological factors like anxiety and depression have also been shown to alter immune reactions like stress, potentially contributing to the onset and persistence of RAS [14].…”
Section: Discussionmentioning
confidence: 99%